Combination of platelet rich plasma and microneedling in the management of atrophic acne scars - Yaseen, Ummer; Shah, Shazia; Bashir, Aquisa (International Journal of Research in Dermatology, 2017)
Background: Acne scars have a lot of psychosocial implications, they are difficult to treat and can cause depression in the affected patient. The objective of the study was to assess the efficacy of combination of platelet rich plasma (PRP) injections and microneedling in the management of acne scars. Methods: Thirty-five patients with atrophic acne scars were enrolled and graded using Goodman and Baron qualitative grading. Platelet rich plasma injection and microneedling were done at 2-week interval alternatively for a total of 6 sessions of each. Acne scars were graded before and 6 months after starting the treatment. Patients own evaluation of improvement was also recorded. Results: A total of 12 patients had grade 4 acne scars, 8 (66.6%) improved to grade 2 and 4 (33.3%) improved to grade 3 scars. Out of 15 grade 3 scars, 8(53.3%) improved to grade 1, 7 (46.6%) improved to grade 2. 8 (100%) grade 2 patients improved to grade 1. All patients were highly satisfied with the results. Conclusions: This combination has shown good results in all grades of acne scars.